The Study of Falak Science in the Qur’an: Analytical Study of Tafsir Al-Misbah - M. Anzaikhan; Muhammad Roni (IAIN Padangsidimpuan, 2021)
The falak science is a discipline of practical astronomy which is more inclined to the relationship between the movement of celestial bodies and the practice of muslim worship. The movement of celestial bodies is often used as an indicator in the implementation of certain worship rituals. The five daily prayers are concerned with the rotation of the earth which causes day and night. The earth and moon revolutions led to the Syamsiah and Qomariah calendars to find out the schedule for the Hajj. The shape of the earth that is round and the sun's light at a certain time can be an indication of the Qibla direction. The definition of falak as the movement of celestial bodies as described above is interesting to study in the Qur’an. This study used a content analysis method of the Qur’an with interpretation media of Tafsir Al-Misbah. There were three concluding phases of this study; First, textual identification of falak verses were found in three words, namely al-falak, al-falaq, and al-fulk. Al-falak means the path of the earth, al-falaq means a cleaver, and al-fulk means ark (sailing ship). Al-Falaq which means the movement of celestial bodies has significance with the theory of nature's qadim. Scientifically, astronomy can prove scientifically that nature predates time